Video Media Health Education on Knowledge, Attitudes, and Personal Hygiene Practices During Menstruation - Ulfah, Nadila Dewi; Nugrahaeni, Dyan Kunthi; Mauliku, Novie Elvinawaty (Jurnal Keperawatan Profesional (KEPO), 2025)
Poor personal hygiene during menstruation had a significant impact on morbidity and complications. Lack of menstrual hygiene awareness was influenced by knowledge and attitudes, as well as external factors such as parental, teacher, peer support, and exposure to information. This study aimed to determine the effect of video-based health education on knowledge, attitudes, and personal hygiene practices during menstruation. The study employed an experimental pre-posttest design. The study population consisted of 98 female students. The sample was divided into two groups: a control group and a treatment group. The results showed differences in the mean scores for knowledge (p-value=0,021), attitudes (p-value=0,000), and practices (p-value=0,000). Parental support (p-value=0,000), teacher support (p-value=0,000), and peer support (p-value=0,000) were identified as confounding factors affecting menstrual hygiene. There was a significant difference in the mean scores of knowledge, attitudes, and practices after the video education intervention. It is recommended that adolescent girls develop clean and healthy living habits by consistently maintaining genital hygiene, both during menstruation and outside of it.